501 Most Notorious Crimes - Donnelley, Paul (London Bounty Books, 2009)
Presents the reader with a line-up of notorious crooks, criminals, villains and thieves, from the mysterious disappearance of Lord Lucan, the assassination of JFK to the treason committed by Guy Fawkes. This book provides an insight into the world's most notorious crimes.
Include Index and Illustration
Keywords: Crime -- Criminals